Lifecycle social impacts of lithium-ion batteries: Consequences and future research agenda for a safe and just transition - Domingues, Ana Mariele [UNESP]; de Souza, Ricardo Gabbay [UNESP]; Luiz, João Victor Rojas [UNESP] (Elsevier, 2024)
Lithium-ion batteries (LIBs) are essential in the low-carbon energy transition. However, the social consequences of LIBs throughout the entire lifecycle have been insufficiently explored in the literature. To address this gap, this study conducted a comprehensive review of peer-reviewed literature, grey literature, and conflicts in the Global Atlas of Environmental Justice associated with LIBs lifecycle. The UNEP Social Lifecycle Assessment framework was utilised for categorisation of stakeholders and social impacts categories. The socio-ecological dynamics and consequences of the global production of LIBs were analysed from the perspective of the Safe and Just operating spaces of the Doughnut Economics (DE). The main results indicate that Worker, Local community, and Society are the most investigated stakeholders, while Consumers, Value chain actors and Children are overlooked. Social impact subcategories related to Safe and healthy living conditions and Access to material resources receive more attention due to social concerns about environmental and social degradation associated with raw material extraction in the LIBs lifecycle. The analysis from DE framework reveals that the increased business as usual production of LIBs can hinder the achievement of a safe and just transition due to undesired socio-ecological consequences, such as increased CO2 emissions, air pollution, land degradation, biodiversity loss, and water pollution that leading to increase poverty, inequality, discrimination (gender and race), health damage, corruption, and conflicts. More research is needed to understand and simulate social consequences of LIBs lifecycle. To this end, a holistic future research agenda is provided.
Keywords: Doughnut economics; Lithium-ion battery; Safe and just transition; Social impacts; Social Lifecycle Assessment